Primary diffuse large B-cell lymphoma (DLBCL) of the sphenoid sinus presenting with oculomotor nerve palsy: A case report and systemic review - Methee Wongsirisuwan; Kritsada Buakate (World Neurosurgery: X)
Introduction: Primary lymphomas of the paranasal sinuses, particularly those affecting the sphenoid sinus, are rare and often diagnostic challenging. Diffuse large B-cell lymphoma (DLBCL) typically presents nonspecific symptoms, resulting in diagnostic delays. Imaging and histopathology evaluation are essential for accurate diagnosis and treatment planning. Case description: A 65-year-old female presented with headache, diplopia, and unilateral ptosis. CT imaging revealed a “ground-glass” appearance with sphenoid sinus erosion, while MRI showed invasion of the cavernous sinus. Endoscopic endonasal resection was performed, and histopathological examination confirmed DLBCL. Following chemotherapy, the patient's headache resolved immediately, and both diplopia and ptosis improved within three months. Methods: A comprehensive literature review was conducted via PubMed up to November 2024 using the terms “sphenoid sinus” and “lymphoma,” Only published, peer-reviewed articles with confirmed diagnoses were included. Conclusion: This report underscores the importance of considering sphenoid sinus lymphoma in the differential diagnosis of skull base lesions presenting with cranial nerve deficits. This rare entity poses significant diagnostic challenges due to its nonspecific clinical and radiologic features. A combined approach of imaging, histopathology, and multidisciplinary treatment offers favorable outcomes.